وسطية الإسلام في التعامل مع المستجدات والنوازل المعاصرة في ضوء أحاديث الإمام الطيب "شيخ الأزهر" التلفزيونية بإشراف عام سماحة مفتي المملكة - الدعدر، مبروك بهي الدين رمضان (مركز البحث العلمي الاسلامي, 2023)
مع التطور المتسارع في حياتنا اليومية، وتتابع النوازل والمستجدات المعاصرة، وفي ظل التنوع والاختلاف المحمود بين البشر في الفهم والاستنباط والتطبيق، فقد حوت الشريعة الإسلامية منهجا متفردا يضمن تحقيق كافة المصالح الضرورية للإنسان، لتحقق التوازن، وتحد من الاختلاف المذموم، أو التناحر، وتئد ما يترتب عليها من صراعات منهجية أو مذهبية أو فكرية. ولما كانت الشريعة الإسلامية بكمالها وتمامها، بنصوصها وأصولها الثوابت، ومتغيراتها المتمثلة في الاجتهادات النابعة من أصالة العلم في تفهم النصوص وإدراك مقاصدها وحسن تطبيقاتها في شتى مجالات الحياة ووقائعها ومتغيراتها وتطوراتها، لم تنفك يوما عن التأكيد على ارتباط أحكامها بفقه الواقع المتغير، مستنيرا بما حوته الشريعة الغراء من الحكم والمقاصد والمصالح التي هي غايات الشارع في التشريع، لتكفل تحقيق أمن واستقرار البلاد والعباد في كل مكان وزمان، وهو ما قرره العلماء العدول قديما وحديثا: بأن التكاليف كلها راجعة إلى مصالح العباد في دنياهم وأخراهم، وأن الشريعة جاءت بتحصيل المصالح وتكميلها، وتعطيل المفاسد وتقليلها، وأنها ترجيح خير الخيرين، ودفع شر الشرين، وتحصيل أعظم المصلحتين بتفويت أدناهما، ودفع أعظم المفسدتين باحتمال أدناهما، وأن أوامر الشرع تتبع المصالح الخالصة أو الراجحة، ونواهيه تتبع المفاسد الخالصة أو الراجحة. ولقد أدرك الأزهر الشريف قبلة العلم والعلماء أهمية هذا عبر التأريخ، وظهر أكثر وضوحا في زماننا المعاصر على يد علماء الأزهر الشريف بمنهج علمي رصين، وجسده شيخ الأزهر في كتبه وفكره وأحاديثه وتصريحاته، ليؤكد الحاجة الماسة والضرورية لأهمية معرفة وتكييف أحكام المستجدات المعاصرة، في كافة المجالات سواء في مسائل العبادات أو المعاملات، والنظر في الوقائع بفهم صحيح، وإدراك لمقاصد الشريعة فيها، في ضوء ما تفرد به الفقه الإسلامي وجسده الإمام الطيب من وسطية واعتدال، لفهم فقه الواقع وتغيراته المتلاحقة، وتحقيق المقاصد الشرعية في الحال والمآل. وتكمن أهمية الموضوع في بيان دور واهتمام الأزهر الشريف بكل مؤسساته العلمية والدعوية لوسطية الإسلام والنظر للمستجدات المعاصرة وتكييفاتها الشرعية في ضوء المقاصد الشرعية للشريعة الغراء، بما يحقق المصالح العامة والخاصة للمكلفين، وارتباطها ارتباطا مطردا بالتشريع في الإسلام، وهو اهتمام في حقيقته يرسم منهج حياة متكامل ومتجدد قائم على ما يحقق مصالح المكلفين، ويضمن لهم حياة كريمة. ولقد جاء الموضوع في مقدمة، ومبحثين، وأربعة مطالب، على النحو الآتي: مقدمة، تحوي أهمية الموضوع وأبرز أهدافه، وعناصره. توطئة: الإمام الطيب وفكره. المبحث الأول: التعريف بمصطلحات الورقة وعلاقاتها الارتباطية، وفيه مطلبان: المطلب الأول: التعريف بمصطلحات الورقة لغة واصطلاحا. المطلب الثاني: العلاقات الارتباطية بين المصطلحات. المبحث الثاني: المستجدات المعاصرة بين فقه الواقع ومقاصد الشريعة في فكر الإمام الطيب، وفيه ثلاث مطالب: المطلب الأول: وسطية الإسلام في التعامل مع المستجدات والنوازل المعاصرة في ضوء حلقات الإمام الطيب. المطالب الثاني: فهم المستجدات المعاصرة في ضوء فقه الواقع وإدراك المقاصد الشرعية. المطلب الثالث: الضوابط العلمية للنظر في المستجدات المعاصرة. الخاتمة وأبرز التوصيات. فهرس المراجع والمصادر. With the rapid development in our daily lives, the succession of calamities and contemporary developments, and in the light of the praiseworthy diversity and difference between humans in understanding, deduction and application, the Islamic Sharia has embraced a unique approach that guarantees the achievement of all the necessary interests of humanity, to achieve balance, reduce reprehensible difference, or rivalry, and destroy what It results in methodological, doctrinal or ideological conflicts. Since the Islamic Sharia in its completeness and completeness, with its texts, its principles, its constants, and its variables represented in the jurisprudence stemming from the originality of science in understanding the texts and realizing its purposes and its good applications in various fields of life, its facts, variables and developments, it has never ceased to emphasize the connection of its provisions with the jurisprudence of the changing reality, enlightened by what the Sharia contains. Glue of wisdom, purposes and interests, which are the goals of the legislator in legislation, to ensure the security and stability of the country and the people in every place and time, and this is what the just scholars have decided past and present: that all costs are due to the interests of the people in their world and the hereafter, and that Sharia came to collect and complement interests, and disrupt Evil and minimizing it, and that it outweighs the good of the two good, and repels the evil of the two evils, and the achievement of the greatest of the two benefits by missing the lesser of them, and the repulsion of the greatest of the two evils by the possibility of the lesser of them, and that the commands of the Sharia follow the pure or preferential interests, and its prohibitions follow the pure or the preponderant evils The honorable Al Azhar, the destination of science and scholars, has realized the importance of this through history, and it has become more evident in our contemporary time at the hands of the honorable Al-Azhar scholars with a sober scientific method. Whether in matters of worship or transactions, looking at the facts with a correct understanding, and realizing the purposes of Sharia in them, in the light of what Islamic jurisprudence and its good Imam body of moderation and moderation are unique to, in order to understand the jurisprudence of reality and its successive changes, and to achieve the legitimate purposes in the moment and the end. The importance of the topic lies in explaining the role and interest of Al-Azhar Al-Sharif in all its scientific and advocacy institutions for the moderation of Islam and the consideration of contemporary developments and their legal adaptations in the light of the legitimate purposes of the glue Sharia, in a way that achieves the public and private interests of the taxpayers, and its continuous link to the legislation in Islam, which is an interest in fact that draws an integrated and renewed life approach It is based on what achieves the interests of the taxpayers and guarantees them a decent life. We will address the subject through an introduction, two chapters, and four demands, as follows: v Introduction, containing the importance of the topic, its main objectives, and its elements. v Foreword: The Good Imam and His Thought. v The first topic: Defining the terms of the paper and their interrelationships, and it has two requirements: ü First Requirement: Defining the terminology of the paper, both linguistically and idiomatically. The second requirement: the associative relationships between the terms. v The second topic: Contemporary developments between the jurisprudence of reality and the purposes of Sharia in the thought of Imam Al-Tayyib, and it contains three demands: ü The first requirement: the moderation of Islam in dealing with contemporary developments and calamities in the light of Imam al-Tayyib› s episodes. • The second demands: Understanding contemporary developments in the light of the jurisprudence of reality and the realization of legitimate purposes. ü The third requirement: the scientific controls for considering contemporary developments. • Conclusion and the most prominent recommendations. • Index of references and sources. Asking God Almighty success, guidance and acceptance.
Keywords: الشريعة الإسلامية -- النوازل المعاصرة -- الطيب، أحمد محمد احمد -- الفتاوى الدينية